Preparation method of metal-doped NiOx nanocrystals, hole transport layer and solar cell
By using metal-doped NiOx nanocrystals as hole transport layer in perovskite solar cells, the problems of uneven distribution, low purity and large particle size of NiOx nanocrystals are solved, efficient hole transport is achieved and the thermal stability and service life of the device are improved.
Patent Information
- Application Number
- CN202211570998.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-08
AI Technical Summary
When preparing the hole transport layer of perovskite solar cells, NiOx nanocrystals are prone to uneven distribution, low purity, large particle size, and redox reactions with perovskites, resulting in poor device performance and stability.
A mixed solution of soluble nickel salt and soluble metal salt was used to react under the addition of ammonia water to obtain a uniform doping precipitate. High-purity metal-doped NiOx nanocrystals were obtained by centrifugation and vacuum drying, and metal-doped NiOx nanocrystals were obtained by sintering.
The uniform distribution, high purity and fine particle size of NiOx nanocrystals are achieved, which reduces the redox reaction with perovskites, improves the thermal stability of the hole transport layer and the stability and service life of perovskite solar cells.
Smart Images

Figure CN116119740B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of perovskite solar cells, and in particular to a preparation method of metal-doped NiOx nanocrystals, a hole transport layer and a solar cell. Background Art
[0002] As the energy crisis becomes increasingly severe, developing new renewable clean energy is an effective solution. Among the many new solar cells, perovskite solar cells stand out for their high efficiency, low raw material prices, and simple preparation methods, and have developed rapidly in the past 10 years.
[0003] At present, the hole transport layer of high-efficiency perovskite solar cells is mainly organic hole transport materials, such as SpiroOMe-TAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), Poly-TPD (poly[bis(4-phenyl)(4-butylphenyl)amine]), PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid), etc. However, the organic hole transport materials are expensive, which limits the further reduction of the preparation cost of perovskite solar cells. At the same time, these organic hole transport materials have the disadvantages of poor thermal stability and hydrophobic surface that is not conducive to the infiltration of perovskite precursors, which limits the large-scale production, long-term working stability and service life of perovskite solar cells. Therefore, inorganic hole transport materials are of great significance to perovskite solar cells due to their good chemical stability, high hole mobility and low preparation cost. Inorganic hole transport materials include: NiO (nickel oxide), CuO2 (cuprous oxide), CuSCN (cuprous thiocyanate), CoO (cobalt oxide), etc.
[0004] NiOx nanocrystals are used as wide-bandgap P-type oxides, which have the advantages of high hole mobility, low parasitic absorption, and good thermal stability, making them ideal materials for hole transport layers. Among them, Ni ions in NiOx are mainly mixed valence states of 2 and 3. However, in the process of using NiOx nanocrystals to prepare hole transport layers, defects such as uneven distribution, low purity, and large particle size of NiOx nanocrystals are prone to occur, which leads to a decrease in the coverage of the ITO substrate, a significant increase in the roughness of the NiOx film, and affects the formation of a high-density perovskite film, affecting device performance; and the low purity of NiOx introduces a large number of defect energy levels, which become carrier recombination centers, resulting in a decrease in efficiency. At the same time, the high-valence Ni ions on the surface of NiOx nanocrystals are prone to redox reactions with perovskites, leading to the degradation of perovskites, thereby affecting the stability and service life of perovskite solar cells. Summary of the invention
[0005] The present invention aims at the technical defects of uneven distribution, low purity, large particle size and easy redox reaction of perovskite when NiOx nanocrystals are used to prepare the hole transport layer of perovskite solar cells. A preparation method of metal-doped NiOx nanocrystals, a hole transport layer and a perovskite solar cell are provided, which have the advantages of high energy conversion efficiency and good thermal stability.
[0006] One of the concepts of the present invention is to use a mixed solution of a soluble nickel salt and a soluble metal salt to react under the addition of ammonia water to obtain a uniformly doped precipitate.
[0007] Specifically, metal ions will undergo ion reaction when ammonia is added. For example, the reaction equation for nickel ions is NH 3 ·H 2 O+Ni 2+ → Ni(OH) 2 ↓. The corresponding magnesium ion reaction equation is NH 3 ·H 2 O+Mg 2+ → +Mg(OH) 2 ↓, and when copper salt or cobalt salt is used, Cu(OH) is generated 2 and Co(OH) 2 etc. precipitation.
[0008] Furthermore, when a suitable ratio of metal ions and nickel ions is added to a mixed solution and ammonia water is added to react, a trace amount of doped precipitate is obtained.
[0009] Specifically, magnesium doping is used as an example. The soluble nickel salt includes Ni(NO 3 ) 2 (Nickel nitrate), NiSO 4 (nickel sulfate) and NiCl 2 (nickel chloride), etc., preferably Ni(NO 3 ) 2 6H 2 O; while soluble magnesium salts include MgCl 2 (Magnesium chloride), MgSO 4 (magnesium sulfate), Mg(NO 3 ) 2 (magnesium nitrate), C 12 H 28 Mg 3 O 23 (magnesium citrate), etc., preferably MgCl 2 .
[0010] Thus, a trace amount of soluble magnesium salt and soluble nickel salt are dissolved in deionized water to obtain a mixed solution of nickel salt and magnesium salt, and then NH 3 ·H 2 O (ammonia water) to obtain the precipitate. The ion reaction equation is:
[0011] NH 3 ·H 2 O+Ni 2+ +Mg 2+ → Ni(OH) 2 ↓+Mg(OH) 2 ↓.
[0012] Furthermore, during the process of dripping the ammonia water, the dripping speed of the ammonia water is controlled so that the particle size of the obtained precipitate is finer and more uniform.
[0013] Furthermore, after the precipitate is precipitated, the precipitate is washed by centrifugation to remove water-soluble ions (such as NH 4 + 、NiO 3 - etc.), to obtain a high-purity mixture of nickel hydroxide and magnesium hydroxide. Further, the precipitate after centrifugal washing is vacuum dried to remove water from the precipitate.
[0014] Furthermore, the vacuum dried precipitate is sintered to obtain magnesium-doped NiOx nanocrystals. The reaction equation is:
[0015] Ni(OH) 2 +Mg(OH) 2+ O 2→ NiO X +MgO x +H 2 O.
[0016] It is worth noting that the present invention realizes the Ni 3+ 、Ni 4+ The passivation of high-valent nickel ions prevents the high-valent Ni ions from reacting with the perovskite grown in the hole transport layer, thereby improving the stability and service life of the perovskite solar cell. At the same time, high-purity and fine-grained metal-doped NiOx nanocrystals will also increase the coverage of the ITO substrate, make the grown perovskite more dense and uniform, and make the film quality higher, thereby further improving the performance of the device.
[0017] In fact, when you want to obtain other metal-doped NiOx nanocrystals, you can use the same processing steps as soluble magnesium salts. For example, when using soluble copper salts, including: CuCl 2 (Copper chloride), CuSO4 (copper sulfate) and Cu(NO 3 ) 2 (copper nitrate); when using soluble cobalt salts, including: CoCl 2 (Cobalt chloride), CoSO 4 (cobalt sulfate) and Co(NO 3 ) 2 (cobalt nitrate).
[0018] Furthermore, the sintering equation is Ni(OH) 2 +Cu(OH) 2+ O 2→ NiO X +CuO x +H 2 O, or, Ni(OH) 2 +Co(OH) 2+ O 2→ NiO X +CoO x +H 2 O, and then obtain copper-doped or cobalt-doped NiOx nanocrystals.
[0019] Therefore, the doping of Cu ions and Co ions can also passivate Ni 3+ 、Ni 4+ High-valent nickel ions such as Mg ions, Cu ions and Co ions can improve the stability and service life of perovskite solar cells. At the same time, since the doping amount of these metal ions is relatively small compared to Ni ions, the passivation effect on Ni ions is basically similar, and there will be no situation that greatly affects the performance of perovskite solar cell devices. Moreover, since they are all soluble metal ions, the ion equations in deionized water are basically the same. The only difference is that due to the melting points of different metal intermediates, the sintering temperatures used during sintering are slightly different.
[0020] Furthermore, since NiOx is in the prepared perovskite solar cell, the higher the thermal radiation, the more likely it is to produce high-valent Ni 3+ and Ni 4+ Therefore, by doping with trace amounts of metal ions, it is possible to inhibit the high-valent NiOx hole mobility. 3+ and Ni 4+ Passivation effect. Because the crystallization reaction of oxides such as Mg, Cu and Co is after that of Ni, the hole transport layer with better thermal stability prepared based on NiOx can be effectively obtained by doping with the above metal ions. Therefore, in theory, as long as the metal ions are soluble in water and undergo precipitation reaction with ammonia water, and the crystallization temperature of their oxides is higher than that of NiOx, they can achieve the passivation of high-valent Ni.3+ and Ni 4+ The passivation effect of high-valent Ni ions such as NiOx can obtain a hole transport layer with better thermal stability. The higher the crystallization temperature, the better the thermal stability effect. Currently, the largest gain for the device is magnesium-doped NiOx nanocrystals.
[0021] In some embodiments, another concept of the present invention is to provide a perovskite solar cell having a hole transport layer prepared using metal-doped NiOx nanocrystals.
[0022] Specifically, the metal-doped NiOx nanocrystals obtained by the present invention are used to prepare the hole transport layer of the perovskite solar cell. The metal-doped NiOx nanocrystals are first dissolved in deionized water to obtain a corresponding solution, and the solution is spin-coated and deposited on a substrate to obtain a hole transport layer of the metal-doped NiOx nanocrystals.
[0023] In some embodiments, based on the obtained hole transport layer of metal-doped NiOx nanocrystals, the present invention also provides a corresponding perovskite solar cell.
[0024] In combination with the above concept, the present invention provides a method for preparing metal-doped NiOx nanocrystals, comprising the following steps:
[0025] S1. Dissolving a soluble nickel salt and a soluble metal salt in deionized water, and stirring thoroughly to form a mixed solution;
[0026] The dissolution ratio of the soluble nickel salt to deionized water is 0.5 mmol / mL, and the molar ratio of metal ions to nickel ions in the mixed solution is 0.001-0.01:1;
[0027] S2, adding ammonia water to the mixed solution at a rate of 30 μL / s-80 μL / s;
[0028] After complete ionization, the molar ratio of ammonium ions to nickel ions is 2.9-3.3:1;
[0029] S3, stir thoroughly and let stand until the precipitate is precipitated;
[0030] S4, using deionized water to centrifuge and wash the precipitated precipitate;
[0031] S5, vacuum drying the precipitate after centrifugal washing;
[0032] S6. Sintering the dried precipitate to obtain metal-doped NiOx nanocrystals.
[0033] Based on the above technical solution, the present invention can obtain metal-doped NiOx nanocrystals with a particle size of 5nm-10nm, high purity and uniform distribution.
[0034] It is worth noting that the doping ratio of metal ions to nickel ions is very important. Too little doping will not be able to achieve the passivation effect on high-valent Ni ions, while excessive doping will affect the device efficiency of NiOx as a hole transport layer. At the same time, the dripping speed of ammonia water is also crucial. Only by controlling the dripping speed of ammonia water can a precipitate with finer particle size be obtained, and then metal-doped NiOx nanocrystals of corresponding particle size can be obtained.
[0035] Further, the soluble metal salts include: soluble magnesium salts, copper salts and cobalt salts;
[0036] When a soluble magnesium salt is used, the dried precipitate is sintered at 270°C-300°C for 2h-4h and at 340°C-370°C for 0.5h-1h to obtain magnesium-doped NiOx nanocrystals;
[0037] When a soluble copper salt is used, in step S6, the dried precipitate is sintered at 185° C. for 0.5 h to 1 h and at 270° C. to 300° C. for 2 h to 4 h to obtain copper-doped NiOx nanocrystals;
[0038] When a soluble cobalt salt is used, in step S6, the dried precipitate is sintered at 60°C-70°C for 0.5h-1h and at 270°C-300°C for 2h-4h to obtain cobalt-doped NiOx nanocrystals.
[0039] The technical solution mainly provides three preferred soluble metal salts to obtain corresponding magnesium-doped NiOx nanocrystals, copper-doped NiOx nanocrystals and copper-doped NiOx nanocrystals.
[0040] It is worth noting that when different metals are doped, there are certain differences in the sintering temperature based on the characteristics of their metal oxides.
[0041] Further, soluble nickel salts include nickel nitrate, nickel sulfate and nickel chloride; soluble metal salts include chlorides, sulfates and nitrates thereof.
[0042] Furthermore, the soluble nickel salt is nickel nitrate hexahydrate, and the soluble metal salt is magnesium chloride;
[0043] Nickel nitrate hexahydrate is 50 mmol, deionized water is 100 ml, magnesium chloride is 0.05 mmol, and ammonia water is 11 mL.
[0044] The present invention adopts the above-mentioned implementation mode to obtain better preparation effect.
[0045] In some embodiments, the sufficient stirring time of step S1 is 20 min-40 min, and the stirring speed is 500 rpm.
[0046] In some embodiments, the ammonia water dropping acceleration in step S2 is 50 μL / s.
[0047] In fact, for different inorganic metal ions, the dripping speed of ammonia water is the same, and the only difference is the total amount of dripping.
[0048] Furthermore, during the process of adding the ammonia water, stirring is performed while adding, and after the addition is completed, the mixture is allowed to stand for 20 minutes to 40 minutes until the ammonia water and the mixed solution of the soluble nickel salt and the magnesium salt fully react and the precipitate is completely precipitated.
[0049] In some embodiments, step S4 is centrifugal washing 3 times, each centrifugation is 5 minutes, and the centrifugal speed is 6000 rpm.
[0050] In some embodiments, step S5, vacuum drying is performed at 100° C. for 8 h to 12 h.
[0051] In some embodiments, the present invention further provides a method for preparing a hole transport layer, comprising the following steps:
[0052] S7, dissolving the metal-doped NiOx nanocrystals in deionized water, stirring thoroughly for 4h-8h, and the solution concentration is 5mg / mL-30mg / mL;
[0053] S8. Use a 0.22 μm filter head to filter the stirred solution, and then ultrasonically treat it for 10 min-20 min. During the ultrasonic process, the water temperature is controlled below 30° C.
[0054] S9. The solution after ultrasonic treatment is spin-deposited onto the substrate through a spin coater to form a hole transport layer.
[0055] Based on the above technical solution, the hole transport layer prepared by the present invention reduces the non-radiative recombination of carriers at the interface between the hole transport layer and the perovskite in the solar cell based on the perovskite material due to the doping of metal elements, thereby improving the device efficiency; and the doping of metal elements will also weaken the NiO x The medium and high valence Ni elements undergo redox reactions with perovskite, thereby improving the thermal stability of perovskite solar cells and extending the life of perovskite solar cells.
[0056] Furthermore, the present invention also provides a solar perovskite cell comprising the above-mentioned hole transport layer. Due to the preparation method of the hole transport layer of the present invention and the characteristics of the metal-doped NiOx nanocrystals, it can be ensured that the hole transport layer of the obtained perovskite solar cell has high thermal stability and good hole mobility, thereby making the perovskite solar cell more stable and more energy-conversion efficient.
[0057] In summary, the preparation method of metal-doped NiOx nanocrystals, the hole transport layer and the solar cell provided by the present invention have at least the following advantages: 1. By controlling the titration rate of ammonia water in a mixed solution of soluble nickel salt and soluble metal salt, NiOx nanocrystals with ultra-small particle size and uniform metal element doping can be obtained, so that the prepared hole transport layer is more compact and has a more uniform thickness; 2. By controlling the doping ratio of metal elements to Ni elements, while ensuring the NiOx hole mobility, the surface defects of NiO nanocrystals are passivated when used in perovskite solar cells, and the oxidation-reduction reaction between high-valent nickel elements and perovskite is avoided, thereby improving the thermal stability and device service life of the hole transport layer and perovskite solar cell prepared by the metal-doped NiOx nanocrystals provided by the present invention; 3. Through operations such as deionized water and centrifugal washing, the obtained metal-doped NiOx nanocrystals have a higher purity, so that the prepared hole transport layer has a high purity, the obtained hole transport layer has fewer energy level defects, and then the hole mobility is improved, so that the energy conversion efficiency of the perovskite solar cell is improved.
[0058] Unless otherwise specified or incompatible therewith, the terms and phrases used herein shall have the following meanings:
[0059] In the present invention, when a numerical range is involved, unless otherwise specified, the two endpoints of the numerical range are included.
[0060] In the present invention, the percentage concentration involved refers to the final concentration unless otherwise specified. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] The present invention will be further described in detail below in conjunction with the accompanying drawings and preferred embodiments, but those skilled in the art will appreciate that these drawings are drawn only for the purpose of explaining the preferred embodiments and therefore should not be used as a limitation on the scope of the present invention. In addition, unless otherwise specified, the drawings are only schematically representing the composition or structure of the described objects and may contain exaggerated displays, and the drawings are not necessarily drawn to scale.
[0062] Figure 1 A schematic diagram of the process for preparing metal-doped NiOx nanocrystals provided by the present invention;
[0063] Figure 2 A schematic diagram of the process for preparing magnesium-doped NiOx nanocrystals provided by the present invention;
[0064] Figure 3 A schematic diagram of the process for preparing copper-doped NiOx nanocrystals provided by the present invention;
[0065] Figure 4 A schematic diagram of the process for preparing cobalt-doped NiOx nanocrystals provided by the present invention;
[0066] Figure 5 Electron microscopic image of the magnesium-doped NiOx nanocrystal provided by the present invention;
[0067] Figure 6 X-ray diffraction image of the magnesium-doped NiOx nanocrystal provided by the present invention;
[0068] Figure 7 X-ray photoelectron spectrum image of magnesium-doped NiOx nanocrystals provided by the present invention;
[0069] Figure 8 The X-ray photoelectron spectrum image of the 1s orbit of the magnesium element in the magnesium-doped NiOx nanocrystal provided by the present invention;
[0070] Fig. 9 Schematic diagram of the magnesium-doped NiOx nanocrystal product provided by the present invention;
[0071] Fig.10 A schematic diagram of the process of preparing a hole transport layer using metal-doped NiOx nanocrystals provided by the present invention;
[0072] Fig.11 A schematic diagram of the device structure of a perovskite solar cell provided by the present invention;
[0073] Fig.12 The J of the magnesium element doped with different molar concentrations provided by the present invention SC Schematic diagram;
[0074] Fig.13 The V doped with magnesium element at different molar concentrations provided by the present invention OC Schematic diagram;
[0075] Fig.14 PCE schematic diagram of magnesium element doped with different molar concentrations provided by the present invention;
[0076] Fig.15 FF schematic diagram of magnesium elements doped with different molar concentrations provided by the present invention;
[0077] Fig.16 A comparison diagram of JV curves of perovskite solar cells with 1% magnesium doping concentration and undoped NiOx nanocrystals provided by the present invention;
[0078] Fig.17 A schematic diagram of PL spectrum (photoluminescence spectrum) curves of a perovskite film of NiOx nanocrystals with a magnesium doping concentration of 1% and without doping provided by the present invention;
[0079] Fig.18 A schematic diagram of TRPL spectrum (time resolved photoluminescence spectrum) curves of a perovskite film of NiOx nanocrystals with a magnesium doping concentration of 1% and an undoped NiOx nanocrystal of the present invention. DETAILED DESCRIPTION
[0080] The following is combined with Figures 1 to 18 , the present invention is described in detail.
[0081] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0082] The present invention provides a method for preparing metal-doped NiOx nanocrystals, a hole transport layer and a solar cell. The metal-doped NiOx nanocrystals have the advantages of uniform doping, small particle size, high purity, etc. The prepared hole transport layer has the advantages of high thermal stability and high hole mobility, thereby improving the thermal stability and energy transmission efficiency of the corresponding perovskite solar cell.
[0083] Figure 1 The schematic diagram of the process for preparing the metal-doped NiOx nanocrystal provided by the present invention is now combined with Figure 1 The preparation method of the metal-doped NiOx nanocrystal provided by the present invention is described.
[0084] Example 1
[0085] First, according to step S1, soluble nickel salt and soluble metal salt are dissolved in deionized water and stirred to form a mixed solution of soluble nickel salt and soluble metal salt. Micromolar amounts of soluble nickel salt and soluble metal salt are fully dissolved in deionized water to form a uniform mixed solution.
[0086] It is worth noting that, in ammonia water, NH 3 ·H 2 O and NH 4 + In order to ensure the full reaction between ammonium ions and nickel ions, it is necessary to ensure that the ammonium ions NH 4+ The molar ratio of ammonium ions to nickel ions is 2.9-3.3:1. Therefore, the total amount of ammonia water added during the actual operation will be slightly excessive so that there is sufficient ammonium ion NH 4 + Reacts with nickel ions and doped metal ions.
[0087] Furthermore, in order to make the mixed solution formed by the soluble nickel salt and the soluble magnesium salt disperse more evenly, the stirring is preferably performed at a speed of 500 rpm for 20 min-40 min during the stirring process.
[0088] Then, in step S2, ammonia water is added dropwise to the mixed solution, and the ammonia water dropping speed is 30 μL / s-80 μL / s. Since the dropping speed of ammonia water is controlled, a trace reaction occurs between the soluble nickel salt and the ammonia water, thereby forming a precipitate with a smaller particle size, thereby finally generating metal-doped NiOx nanocrystals with a particle size of 5nm-10nm.
[0089] Furthermore, during the dropwise addition of ammonia water, stirring is performed.
[0090] Furthermore, the ammonia water dropping speed is preferably 50 μL / s.
[0091] Then, in step S3, after the ammonia water is added, the mixture is stirred sufficiently, and after the reaction is complete, the mixture is allowed to stand to allow the precipitate to be fully separated out.
[0092] Furthermore, the standing time is preferably 20 min-40 min.
[0093] Then, in step S4, the precipitate is centrifuged and washed with deionized water. The impurity ions attached to the surface of the precipitate, such as NH 4 + 、NiO 3 - , washed to ensure the purity of NiOx nanocrystals in the precipitate.
[0094] Further, the precipitate was placed in a centrifuge tube and washed by centrifugation for 3 times, each time for 5 minutes, and the centrifugal speed was 6000 rpm.
[0095] Then, in step S5, the precipitate after centrifugal washing is vacuum dried to remove moisture in the precipitate, and the vacuum environment also ensures the purity of the precipitate after drying.
[0096] Further, vacuum drying is performed in a vacuum drying oven at 100° C. for 8 h to 12 h.
[0097] Finally, in step S6, the dried precipitate is sintered in a muffle furnace, sintered at 270° C.-300° C. for 2 h-4 h and sintered at 340° C.-370° C. for 0.5 h-1 h, to obtain metal-doped NiOx nanocrystals.
[0098] Example 2
[0099] See Figure 2 As shown, a method for preparing magnesium-doped NiOx nanocrystals is provided.
[0100] The soluble nickel salt is preferably Ni(NO 3 ) 2 6H2 O, soluble magnesium salt is preferably MgCl 2 .
[0101] When ammonia water is added dropwise, the ion reaction formula is NH 3 ·H 2 O+Ni 2+ +Mg 2+ → Ni(OH) 2 ↓+Mg(OH) 2 ↓, the reaction formula during sintering is Ni(OH) 2 +Mg(OH) 2+ O 2→ NiO X +MgO x +H 2 O, thereby obtaining Mg-doped NiOx nanocrystals.
[0102] Example 3
[0103] See Figure 3 As shown, a method for preparing magnesium-doped NiOx nanocrystals is provided.
[0104] The soluble nickel salt is preferably Ni(NO 3 ) 2 6H 2 O, the soluble magnesium salt is preferably CuCl 2 .
[0105] When ammonia water is added dropwise, the ion reaction formula is NH 3 ·H 2 O+Ni 2+ +Cu 2+ → Ni(OH) 2 ↓+Cu(OH) 2 ↓, the reaction formula during sintering is Ni(OH) 2 +Cu(OH) 2+ O 2→ NiO X +CuO x +H 2 O, thereby obtaining copper-doped NiOx nanocrystals.
[0106] Example 4
[0107] See Figure 4 As shown, a method for preparing cobalt-doped NiOx nanocrystals is provided.
[0108] The soluble nickel salt is preferably Ni(NO 3 ) 2 6H 2 O, the soluble magnesium salt is preferably CoCl2 .
[0109] When ammonia water is added, the ion reaction formula is NH 3 ·H 2 O+Ni 2+ +Co 2+ → Ni(OH) 2 ↓+Co(OH) 2 ↓, the reaction formula during sintering is Ni(OH) 2 +Co(OH) 2+ O 2→ NiO X +CoO x +H 2 O, thereby obtaining cobalt-doped NiOx nanocrystals.
[0110] Furthermore, the present invention is specifically explained using magnesium-doped NiOx nanocrystals.
[0111] See Figure 5 As shown, it can be seen that the magnesium-doped NiOx nanocrystals are evenly distributed under an electron microscope and have a small particle size of about 5nm-10nm. At the same time, from the distribution of magnesium elements under an electron microscope, it can be seen that magnesium elements are evenly doped in NiOx nanocrystals and have a good passivation effect on high-valent Ni elements.
[0112] For further information, see Figure 6-8 As shown, the prepared magnesium-doped NiOx nanocrystalline powder has an X-ray diffraction pattern (XRD) and an X-ray photoelectron spectroscopy (XPS) pattern, which indicates that the magnesium element has been successfully doped into the lattice of the NiOx nanocrystals.
[0113] For further information, see Fig. 9 As shown, Fig. 9 Schematic diagram of the final prepared metal-doped NiOx nanocrystals.
[0114] In some embodiments, the present invention also provides a method for preparing a hole transport layer using the metal-doped NiOx nanocrystals obtained by the preparation method of the present invention.
[0115] See Fig.10 As shown, S7, disperse the metal-doped NiOx nanocrystals in deionized water at a ratio of 5mg / mL-30mg / mL, and stir them thoroughly for 4h-8h; S8, use a 0.22μm filter head to filter the stirred solution, and then ultrasonically treat it for 10min-20min, and control the water temperature below 30°C during the ultrasonic process; S9, rotate and deposit the solution after ultrasonic treatment onto the substrate through a gelator to prepare a hole transport layer of metal-doped NiOx nanocrystals.
[0116] It is worth noting that the 0.22 μm filter head is used to obtain a uniform mixed solution with smaller particle size and is not a specific limitation.
[0117] Since the metal-doped NiOx nanocrystals provided by the present invention have small particle size and uniform distribution, and benefit from the passivation effect of magnesium on high-valent nickel elements, the hole mobility of the prepared hole transport layer will be improved and its thermal stability will be improved.
[0118] In some embodiments, the present invention also provides a perovskite solar cell comprising the above-mentioned hole transport layer.
[0119] For details, see Fig.11 As shown, the perovskite solar cell composed of metal-doped NiOx nanocrystals includes: a metal electrode, an electron transport layer, a perovskite layer, a metal-doped NiOx nanocrystal hole transport layer and a substrate arranged in sequence. Among them, the metal electrode layer uses 100nm Ag as the cathode; 20nm C60 is used as the electron transport layer, and 7nm BCP (bathocuproin) is used as the interface modification, and the above materials are all prepared by thermal evaporation; the perovskite layer uses a 1.67eV wide band gap perovskite layer, the chemical composition is FA0.8Cs0.2Pb(I0.8Br0.2)3, and is prepared by one-step anti-solvent spin coating; and indium-doped tin oxide is used as the transparent electrode layer.
[0120] Example 5
[0121] In this embodiment, the corresponding perovskite solar cell is prepared by using magnesium-doped NiOx nanocrystals prepared in a molar ratio of magnesium ions to nickel ions of 0.001 (ie, 0.1%, to make the chart more intuitive, the percentage is used to represent it): 1.
[0122] The PCE (energy conversion efficiency, hereinafter referred to as PCE) of the perovskite solar cell provided in this embodiment is 18.2%, V OC (Open circuit voltage, referred to as V OC ) is 1.14V, J SC (Short-circuit current, hereinafter referred to as J SC ) is 20.76 mA / cm 2 , FF (filling factor, hereinafter referred to as FF) is 0.772.
[0123] Example 6
[0124] In this embodiment, magnesium-doped NiOx nanocrystals prepared with a molar ratio of magnesium ions to nickel ions of 0.005 (0.5%):1 are used to prepare the corresponding perovskite solar cell.
[0125] The PCE of the perovskite solar cell provided in this embodiment is 18.9%, V OCis 1.16V, J SC 20.86 mA / cm 2 , FF is 0.812.
[0126] Example 7
[0127] In this embodiment, magnesium-doped NiOx nanocrystals prepared with a molar ratio of magnesium ions to nickel ions of 0.01 (1%):1 are used to prepare the corresponding perovskite solar cell.
[0128] The PCE of the perovskite solar cell provided in this embodiment is 19.7%, V OC is 1.17V, J SC 21.11 mA / cm 2 , FF is 0.815.
[0129] Example 8
[0130] In this embodiment, magnesium-doped NiOx nanocrystals prepared with a molar ratio of magnesium ions to nickel ions of 0.05 (5%):1 are used to prepare the corresponding perovskite solar cell.
[0131] The PCE of the perovskite solar cell provided in this embodiment is 18.5%, V OC is 1.16V, J SC 20.53mA / cm 2 , FF is 0.788.
[0132] Example 9
[0133] In this embodiment, magnesium-doped NiOx nanocrystals prepared with a molar ratio of magnesium ions to nickel ions of 0.1 (10%):1 are used to prepare the corresponding perovskite solar cell.
[0134] The PCE of the perovskite solar cell provided in this embodiment is 18.1%, V OC is 1.15V, J SC 20.53mA / cm 2 , FF is 0.788.
[0135]
[0136] The parameters in the above table are the arithmetic mean values of 30 sample points. According to the above experimental data, when the molar ratio of magnesium ions to nickel ions is 0.01:1 (i.e. 1%), the device performance of the perovskite solar cell obtained by the prepared magnesium-doped NiOx nanocrystals is the best, and its PCE, V OC , J SC and FF parameters have been improved, see Figure 12-15 shown.
[0137] Now take the magnesium doping molar ratio of 1% as an example, Fig.16 The JV curve is shown in the figure. The Target curve (Mg doping molar ratio is 1%) is on the top and the Control curve (undoped) is on the bottom. It can be clearly seen that when the Mg doping molar ratio is 1%, the device efficiency is increased from 18% to 20%, indicating that the solar perovskite solar cell prepared by Mg doped NiOx nanocrystals can significantly improve the photoelectric conversion efficiency of the device.
[0138] Solar cell parameters NiOx doped with 1% Mg by mole ratio Undoped NiOx PCE(%) 20.59 18.35 VOC(V) 1.17 1.08 JSC(mA / cm2) 21.57 20.91 FF 0.816 0.812
[0139] The above table is a detailed parameter comparison of a single device. The efficiency of the device prepared by 1% molar ratio of magnesium-doped NiOx nanocrystals is increased by about 2.24% compared with the efficiency of the device prepared by NiOx nanocrystals without any doping.
[0140] Further, NiO nanocrystals doped with 1% Mg molar ratio and undoped NiO nanocrystals were used as control experiments. Fig.17 and Fig.18 As shown. Fig.17 From the PL curve, it can be seen that the perovskite film deposited on the NiOx substrate with a 1% Mg doping molar ratio has a significantly higher luminescence intensity, indicating that the non-radiative recombination of carriers has been effectively suppressed. Fig.18 From the TRPL curve, it can be seen that the carrier lifetime of the perovskite film on the NiOx substrate with a magnesium doping molar ratio of 1% is longer, that is, the carrier has a slower quenching rate at the interface, which verifies that NiOx nanocrystals doped with inorganic metal magnesium can effectively passivate high-valent Ni 2+ 、Ni 3+ etc., to avoid degradation of perovskite.
[0141] Therefore, the perovskite solar cell device deposited on the NiOx nanocrystal substrate doped with inorganic metal magnesium has better performance and stability and longer service life.
[0142] The present invention is described in detail above. The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the present invention and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing metal-doped NiOx nanocrystals, characterized in that: The following steps are involved: S1. Dissolve a soluble nickel salt and a soluble metal salt in deionized water, and stir thoroughly to form a mixed solution; The dissolution ratio of the soluble nickel salt to deionized water is 0.5 mmol / mL, and the molar ratio of metal ions to nickel ions in the mixed solution is 0.001-0.01:1; S2, adding ammonia water to the mixed solution at a rate of 30 μL / s-80 μL / s; After complete ionization, the molar ratio of ammonium ions to nickel ions is 2.9-3.3:1; S3, stir thoroughly and let stand until the precipitate is precipitated; S4, using deionized water to centrifuge and wash the precipitated precipitate; S5, vacuum drying the precipitate after centrifugal washing; S6, sintering the dried precipitate to obtain metal-doped NiOx nanocrystals; Soluble metal salts include: soluble magnesium salts, copper salts and cobalt salts; When a soluble magnesium salt is used, the dried precipitate is sintered at 270°C-300°C for 2h-4h and at 340°C-370°C for 0.5h-1h to obtain magnesium-doped NiOx nanocrystals; When a soluble copper salt is used, in step S6, the dried precipitate is sintered at 185° C. for 0.5 h to 1 h and at 270° C. to 300° C. for 2 h to 4 h to obtain copper-doped NiOx nanocrystals; When a soluble cobalt salt is used, in step S6, the dried precipitate is sintered at 60°C-70°C for 0.5h-1h and at 270°C-300°C for 2h-4h to obtain cobalt-doped NiOx nanocrystals.
2. The method for preparing metal-doped NiOx nanocrystals according to claim 1, characterized in that: Soluble nickel salts include nickel nitrate, nickel sulfate and nickel chloride; soluble metal salts include their chlorides, sulfates and nitrates.
3. The method for preparing metal-doped NiOx nanocrystals according to claim 2, characterized in that: The soluble nickel salt is nickel nitrate hexahydrate, and the soluble metal salt is magnesium chloride; Nickel nitrate hexahydrate is 50 mmol, deionized water is 100 ml, magnesium chloride is 0.05 mmol, and ammonia water is 11 mL.
4. The method for preparing metal-doped NiOx nanocrystals according to claim 1, characterized in that: In step S1, the sufficient stirring time is 20 min-40 min, and the stirring speed is 500 rpm.
5. The method for preparing metal-doped NiOx nanocrystals according to claim 1, characterized in that: In step S2, the ammonia water droplet acceleration is 50 μL / s.
6. The method for preparing metal-doped NiOx nanocrystals according to claim 1, characterized in that: In step S4, centrifugal washing is performed three times, each time for 5 minutes, and the centrifugal speed is 6000 rpm.
7. The method for preparing metal-doped NiOx nanocrystals according to claim 1, characterized in that: In step S5, vacuum drying is performed at 100°C for 8 hours to 12 hours.
8. A method for preparing a hole transport layer, characterized in that: The hole transport layer is prepared by using the metal-doped NiOx nanocrystal prepared by the preparation method according to any one of claims 1 to 7, comprising the following steps: S7, dissolving the metal-doped NiOx nanocrystals in deionized water, stirring thoroughly for 4h-8h, and the solution concentration is 5mg / mL-30mg / mL; S8. Use a 0.22 μm filter head to filter the stirred solution, and then ultrasonically treat it for 10 min-20 min. During the ultrasonic process, the water temperature is controlled below 30° C. S9. The solution after ultrasonic treatment is spin-deposited onto the substrate through a spin coater to form a hole transport layer.
9. A perovskite solar cell, characterized in that: It comprises a hole transport layer obtained by the method for preparing a hole transport layer as claimed in claim 8.
Citation Information
Patent Citations
Tin-based perovskite solar cell with a hole transport layer and preparation method thereof
CN112186107A